Does Local Ownership of Vacant Land Reduce Crime?: An Assessment of Chicago's Large Lots Program. Issue 1 (2nd January 2021) - Stern, Matthew; Lester, T. William
Abstract: Problem, research strategy, and findings: Urban vacancy presents myriad concerns for American legacy cities, including cyclical disinvestment, property value and tax revenue decimation, increased crime, and high management costs. To address these problems, the City of Chicago (IL) has sold more than 1, 200 vacant city-owned parcels in distressed communities for $1 through its Large Lots Program since 2014. Program buyers must be same-block landowners, although they are not required to live nearby. In this study we estimate the true distance between buyers and their parcels and perform a block-level difference-in-differences analysis to explore whether the program reduces crime. We find that same-neighborhood buyers have purchased 69% of parcels. Overall, sales reduce block-level crime rates by 3.5%, but sales to neighborhood residents decrease crime rates by 6.8%. These findings are agnostic to what buyers actually do with their land and could be enhanced with a better understanding of which owners achieve productive reuse. Takeaway for practice: Side yard programs seek solutions to urban vacancy via decentralized community reinvestment but have so far been relatively untested. We demonstrate that Chicago's Large Lots Program has reduced crime while providing reinvestment and wealth-building opportunities. However, attention should be paid to how program rules and outreach efforts affect how "local" parcel buyers are. More research is needed to evaluate the broader impacts of side yard programs, such as on wealth building and community redevelopment.